Analysis of heat and mass transfer by CFD for performance enhancement in direct contact membrane distillation - Yu, Hui (2013)
A comprehensive analysis on the dominant effects for heat and mass transfer in the direct contact membrane distillation (DCMD) process has been performed with the aid of computational fluid dynamics (CFD) simulations for hollow fiber modules without and with annular baffles attached to the shell wall. Potential enhancement strategies under different circumstances have been investigated.